IMPLIKATUR DAN PRESUPOSISI DALAM INTERAKSI BERBAHASA (STUDI KASUS TERHADAP TUTURAN TOKOH UTAMA DALAM DWILOGI FILM BEFORE SUNRISE DAN BEFORE SUNSET) - , Eliana Candrawati, Dr. F.X. Nadar, M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This research is aimed at finding and describing conversational implicatures along with their implication, and presuppositions including their implications to reach full comprehension in communication. This descriptive qualitative research was conducted through three steps